Environmental effects and seismogenic source characterization of the December 2020 earthquake sequence near Petrinja, Croatia. Issue 2 (26th March 2022) - Baize, S; Amoroso, S; Belić, N; Benedetti, L; Boncio, P; Budić, M; Cinti, F R; Henriquet, M; Jamšek Rupnik, P; Kordić, B; Markušić, S; Minarelli, L; et al.
SUMMARY: On 29 December 2020, a shallow earthquake of magnitude M w 6.4 struck northern Croatia, near the town of Petrinja, more than 24 hr after a strong foreshock ( M L 5). We formed a reconnaissance team of European geologists and engineers, from Croatia, Slovenia, France, Italy and Greece, rapidly deployed in the field to map the evidence of coseismic environmental effects. In the epicentral area, we recognized surface deformation, such as tectonic breaks along the earthquake source at the surface, liquefaction features (scattered in the fluvial plains of Kupa, Glina and Sava rivers), and slope failures, both caused by strong motion. Thanks to this concerted, collective and meticulous work, we were able to document and map a clear and unambiguous coseismic surface rupture associated with the main shock. The surface rupture appears discontinuous, consisting of multi-kilometre en échelon right stepping sections, along a NW–SE striking fault that we call the Petrinja-Pokupsko Fault. The observed deformation features, in terms of kinematics and trace alignments, are consistent with slip on a right lateral fault, in agreement with the focal solution of the main shock. We found mole tracks, displacement on faults affecting natural features (e.g. drainage channels), scarplets and more frequently breaks of anthropogenic markers (roads, fences). The surface rupture is observed over a length of ∼13 km from end-to-end, with a maximum displacement of 38 cm, and an average displacement of ∼10 cm. Moreover, the liquefaction extends over an area of nearly 600 km 2 around the epicentre. Typology of liquefaction features include sand blows, lateral spreading phenomenon along the road and river embankments, as well as sand ejecta of different grain size and matrix. Development of large and long fissures along the fluvial landforms, current or ancient, with massive ejections of sediments is pervasive. These features are sometimes accompanied by small horizontal displacements. Finally, the environmental effects of the earthquake appear to be reasonably consistent with the usual scaling relationships, in particular the surface faulting. This rupture of the ground occurred on or near traces of a fault that shows clear evidence of Quaternary activity. Further and detailed studies will be carried out to characterize this source and related faults in terms of future large earthquakes potential, for their integration into seismic hazard models.